Encyclopedia of portal technologies and applications - Tatnall, Arthur (Hershey, PA : Information Science Reference, 2007)
'This book offers complete coverage of the nature, characteristics, advantages, limitations, design, and evolution of Web portals. Other topics include semantic portals, philosophical portal issues, and personal portals. This authoritative encyclopedia encompasses the economics of setting up and using personal portals, knowledge management, strategic planning, user acceptance, security and the law'--Provided by publisher.
Pesanan sementara Yuha Associates Sdn. Bhd.
Includes bibliographical references and index.
Keywords: Web portals -- Encyclopedias; World Wide Web -- Encyclopedias; Knowledge management -- Encyclopedias; Online information services -- Encyclopedias; Computer network resources -- Encyclopedias